HUBUNGAN KECEPATAN DAN KELINCAHAN DENGAN KEMAMPUAN MENGGIRING BOLA TEAM SEPAK BOLA DI SMK TARUNA SATRIA PEKANBARU - Teguh Alvarisi; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problem in this research that speed and agility with the ability to herd on the soccer team at the Pekanbaru Cadets Vocational School. This type of research is a type of correlation research. The population of this research was the Pekanbaru Satria Vocational School Team, which numbered 20 people. The sampling technique is taken entirely (total sampling). So this sampling technique is fully 20 people from the Satria Taruna Vocational School Pekanbaru. Based on the research that has been done, it can be obtained from the correlation of Pekanbaru Satria Taruna Vocational School Team where the first analysis between Speed and Ball X1 and Y Ability where rtab at a significant level ɑ (0.05) = r_count (0.102 ) > r_tab (0.456), means the hypothesis is not accepted and there is no significant correlation between speed and the ability to accompany the Taruna Satria VOCATIONAL SCHOOL of Pekanbaru soccer team. From the calculation of the analysis of both X2 and Y, where r_tab at a significant level ɑ (0.05) = means r_count (0.656) > r_tab (0.456), meaning the hypothesis is accepted and there is a significant correlation between agility and the ability to dribble the Taruna Satria Vocational School Pekanbaru football team . The third analysis of the correlation of speed (X1) agility (X2) with dribbling ability (Y) where rtab at a significant level ɑ (0.05) = r_count (0.660) > r_tab (0.456), it can be concluded that the relationship between (X1) and (X2) with (Y) or the correlation between speed and agility with dribbling ability has a strong interpretation.Key Words: Speed, Agility and Herding Ball